(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. La Chiesa Ortodossa del Patriarcato di Mosca come confessione multinazionale - 3. Le disposizioni rituali di contrasto alla pandemia da parte delle Chiese auto amministrate appartenenti al Patriarcato di Mosca - 4. La Chiesa Ortodossa Rumena di fronte alla pandemia - 5. Il Patriarcato Ecumenico e l’orientamento delle Chiese Autocefale. Orthodoxy, Pandemic, and Legislation of Eastern European Countries for the Safeguard of Health ABSTRACT: The article examines the attitude and the regulations adopted by the clergy and believers of the major Orthodox Churches in relation to the pandemic. In this perspective, the modifications requested by States in the field of public religious functions and ritual celebrations are the object of the current analysis. Furthermore, the modalities of the administration of the sacraments and the carrying out of religious functions in relation to the protection of religious freedom are critically assessed and commented.